Glucose-induced [Ca2+]i oscillations in β cells are composed of trains of spikes within a subplasmalemmal microdomain. (November 2021) - Langlhofer, Georg; Kogel, Alexander; Schaefer, Michael
Highlights: Slow glucose-induced [Ca 2+ ]i oscillations in β cells are composed of bursts of Ca 2+ spikes Ca 2+ dynamics and concentrations differ between the cytosol and subplasmalemmal space Abstract: Electrical activity and oscillations of cytosolic Ca 2+ concentrations ([Ca 2+ ]i ) that trigger insulin release in response to glucose are key functions of pancreatic β cells. Although oscillatory Ca 2+ signals have been intensively studied in β cells, their lower frequency did not match that of electrical activity. In addition, the measured peak [Ca 2+ ]i did not reach levels that are typically required by synaptotagmins to elicit the release of insulin-containing vesicles in live-cell experiments. We therefore sought to resolve the Ca 2+ dynamics in the subplasmalemmal microdomain that is critical for triggering fast exocytosis. Applying total internal reflection fluorescence (TIRF) microscopy in insulin-producing INS-1E and primary mouse β cells, we resolved extraordinary fast trains of Ca 2+ spiking (frequency > 3 s −1 ) in response to glucose exposure. Using a low-affinity [Ca 2+ ]i indicator dye, we provide experimental evidence that Ca 2+ spikes reach low micromolar apparent concentrations in the vicinity of the plasma membrane. Analysis of Ca 2+ spikes evoked by repeated depolarization for 10 ms closely matched the Ca 2+ dynamics observed upon glucose application. To our knowledge, this is the first study that experimentally demonstrates Ca 2+ spikes in β cells with velocities that resemble those of bursting or continuously appearing trains of action potentials (APs) in non-patched cells. Graphical abstract: Image, graphical abstract